ANALYZIS OF A MODERN SITUATION OF THE LOCAL BUDGETS IN UKRAINE - Тымоць, Мирослава (SWorldJournal, 2022)
It is analyzed the modern state of local budgets in Ukraine in this article. It is researched the dynamics of the income and the expenditure parts of the budgets of the organs of the local municipality.It is grounded the reasons of a structural changes i